Exploration of the effect of product differentiation on the level of visitor loyalty in the Mojokerto Mountain Region - Khoiruddin Khoiruddin; Chairul Anam (Trigin Publisher, 2023)
Because there are so many tourist attractions in Mojokerto, there is even more rivalry amongst them. To remain in business, one must thus be able to retain consumers, which requires the implementation of an effective marketing plan. The objectives of this research are to investigate and evaluate the impact of product differentiation on customer satisfaction, the impact of product differentiation on customer loyalty, the impact of customer satisfaction on customer loyalty, and the indirect impact of product differentiation on customer loyalty through customer satisfaction in the Mojokerto mountain region of East Java. 110 visitors make up the study's sample. The study's method of sampling is incidental sampling. Utilizing questionnaires, data were gathered and verified for accuracy and consistency. SPSS Windows version 24 is utilized to perform linear regression analysis on the data provided in this study. Regression analysis findings indicated that the initial product differentiation significantly improved customer satisfaction. Second, client loyalty directly benefits from product differentiation. Third, there was a notable positive correlation between customer loyalty and satisfaction. Fourth, by a favorable indirect impact on customer satisfaction, product differentiation significantly increased customer loyalty.